Magnetic-Assisted Control of Eggs and Embryos via Zona Pellucida-Linked Nanoparticles - García Vázquez, Francisco Alberto; Garrappa, Gabriela; Luongo, Chiara; Hamze, Julieta Gabriela; Caballero, María; Marco-Jiménez, Francisco; Antón, José Salvador Vicente; Molina-Cuberos, Gregorio J.; Jiménez Movilla, María (Wiley, 2025)
Eggs and embryo manipulation is an important biotechnological challenge to enable positioning, entrapment, and selection of reproductive cells to advance into a new era of nature-like assisted reproductive technologies. Oviductin (OVGP1) is an abundant protein in the oviduct that binds reversibly to the zona pellucida, an extracellular matrix that surrounds eggs and embryos. Here, the study reports a new method coupling OVGP1 to magnetic nanoparticles (NP) forming a complex (NPOv). NPOv specifically surrounds eggs and embryos in a reversible manner. Eggs/embryos bound to NPOv can be moved or retained when subjected to a magnetic force, and interestingly only mature-competent eggs are attracted. This procedure is compatible with normal development following gametes function, in vitro fertilization, embryo development and resulting in the birth of healthy offspring. The results provide in vitro proof-of-concept that eggs and embryos can be precisely guided in the absence of physical contact by the use of magnets.